New Signal Processing Method to Improve Image Quality of RGBW Display. Issue 1 (June 2014) - Kabe, Masaaki; Nagatsuma, Toshiyuki; Higashi, Amane; Nakahara, Tae; Ikeda, Kojiro; Goto, Fumitaka; Sakaigawa, Akira
Abstract In this paper, the analysis and cause of image quality deterioration of an RGBW display is described. We have found that some distortions are caused by the combination of luminance distribution in a pixel scale and the human visual system. A newly‐developed RGBW calculation is proposed to solve this problem.